2008
DOI: 10.2527/jas.2007-0533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding high-temperature, microtime-treated diets with different lipid sources on conjugated linoleic acid formation in finishing Hanwoo steers1

Abstract: The present study was conducted to examine the effects of different plant oils or plant oil mixtures and high-temperature, microtime processing (HTMT) on the CLA content in Hanwoo steers. Experiment 1, consisting of 3 in vitro trials, was conducted to determine how the biohydrogenation of C18 fatty acids and CLA production were affected by fat sources (tallow, soybean oil, linseed oil, or mixtures of soybean oil and linseed oil) or HTMT treatment in the rumen fluid. The results showed that HTMT was capable of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Additionally, SFA, MUFA and PUFA were 49.08, 42.84 and 6.86 g/100 g, respectively. It was noted that the Hanwoo in the study of Xu et al (2008) had more SFA and C18:2n-6 than the Hanwoo in our experiment. This may be ascribed to the difference in the diet used and the higher proportion of concentrate and roughage given to the animal in the experiment of Xu et al (2008).…”
Section: Fatty Acid Compositionmentioning
confidence: 77%
See 1 more Smart Citation
“…Additionally, SFA, MUFA and PUFA were 49.08, 42.84 and 6.86 g/100 g, respectively. It was noted that the Hanwoo in the study of Xu et al (2008) had more SFA and C18:2n-6 than the Hanwoo in our experiment. This may be ascribed to the difference in the diet used and the higher proportion of concentrate and roughage given to the animal in the experiment of Xu et al (2008).…”
Section: Fatty Acid Compositionmentioning
confidence: 77%
“…The total fatty acid was comprised of 43% SFA, 53% MUFA and 3% PUFA. Xu et al (2008) observed that in 26 mon old Hanwoo steers (644 kg) fed ground concentrate and alfalfa hay on a 9:1 ratio for a 2 mon feeding period, the quantity (g/100 g) of the major fatty acid components of m. longissimus are as follows: C16 (26.49), C16:1 (2.78), C18 (16.77), C18:1n-9 (34.57), C18:2n-6 (6.52), C18:3n-3 (0.20). Additionally, SFA, MUFA and PUFA were 49.08, 42.84 and 6.86 g/100 g, respectively.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…As already shown in studies with 130 to 160°C roasted oilseeds 8, 9 or with heated oil 1, 30, heating offered a partial protection of PUFA from BH in this study. With extruded oilseeds, some protection of PUFA was sometimes observed 6, 7 but not always 11, 12.…”
Section: Discussionmentioning
confidence: 99%
“…The high ATGL activity in BAT together with the impaired thermogenesis in ATGL-null mice, while HSL-null mice exhibited normal thermogenesis, suggest that ATGL is essential for the provision of FA as substrate for BAT thermogenesis (Zechner et al, 2009). To date, only HSL has been identified in bovine WAT through its mRNA abundance (Bonnet et al, 1998;Sumner and Mcnamara, 2007;Xu et al, 2008) and its activity (Sprinkle et al, 1998;Kazala et al, 2003). The thermogenic protein UCP1, together with enzymes involved in the citric acid cycle and the respiratory chain, are expressed in bovine foetal BAT, allowing FA oxidation and heat production (Casteilla et al, 1989;Smith et al, 2004;Hocquette et al, 2006).…”
Section: Dynamics Of At Growthmentioning
confidence: 99%